Factors contributing for Malaysian employees’ willingness to accept international assignment - Mansor, Zuraina; Adnan, Nadia (Faculty of Economics and Management, Universiti Putra Malaysia, 2014)
The decision to take an International Assignment (IA) is always a difficult situation for any individual. IAs are often taken for enjoyment, travelling, exploring and challenging oneself with new environments in a different country. At the same time, people are confused, worried, and not ready to face the obstacles, especially those associated with unfamiliarity and, more importantly, the way they live and work. The study aims to identify the factors that could influence Malaysian human resources when considering themselves for an IA. This is important because there is a growing demand for global talent, yet the number of failure assignments is increasing. The study was conducted on 130 Malaysian respondents who were currently working with multinational company (MNCs) or for government sector or any other company type that has a business or subsidiaries outside Malaysia. Data were analyzed using the descriptive analysis and multiple regression analysis. The result shows that two factors—cultural factor and organizational factors—can influence Malaysians’ willingness to take IA.